A physicochemical model of reaction kinetics supports peroxyl radical recombination as the main determinant of the FLASH effect. (December 2020) - Labarbe, Rudi; Hotoiu, Lucian; Barbier, Julie; Favaudon, Vincent
Highlights: A kinetic model is proposed to explain normal tissue sparing by FLASH irradiation. The model takes into consideration and solves 9 differential rate equations, based on published values of the rate constants of free radical and enzymatic reactions involving reactive oxygen species in a cellular context. For different doses, dose-rates and oxygen concentrations, the area-under-the-curve (AUC) drawn from the time-dependent evolution of peroxyl radical intermediates RO O ., correlates the normal tissue complications (NTCP) determined from the outcomes of published FLASH studies. Abstract: Background and purpose: FLASH radiotherapy, a technique based on delivering large doses in a single fraction at the micro/millisecond timescale, spares normal tissues from late radiation-induced toxicity, in an oxygen-dependent process, whilst keeping full anti-tumor efficiency. We present a theoretical model taking into account the kinetics of formation and decay of reactive oxygen species, in particular of organic peroxyl radicals RO O . formed by addition of O 2 to primary carbon-centred radicals R . and known to play a major role at the origin radio-induced complications. Materials and methods: The model focuses on the time-dependent evolution of radiolytic products in living matter exposed to continuous irradiation at dose-rates in the range 1 0 - 3 - 1 0 7 G y · s - 1 . The 9 differential rate equations resulting from the radiolytic and enzymatic reactions network were solved using the published values of these reactions rate constants in a cellular environment. Results: The model suggests a correlation between the area-under-the-curve of time-evolving [ R O O . ] and the probability of normal tissue complications. The model does not lend weight to the hypothesis of transient oxygen depletion as a main determinant of FLASH but rather suggests a major role of radical–radical recombination. Conclusion: The model gives support to the reduction of RO O . lifetime as the main root of FLASH and compares favorably with published experimental results. We conclude that any process - in this case radical recombination - that shortens the lifetime or limits the radiolytic yield of RO O . is likely to protect normoxic tissues against the deleterious effects of radiation.